2013
DOI: 10.1242/jcs.131896
|View full text |Cite
|
Sign up to set email alerts
|

Expression of oleosin and perilipins in yeast promote formation of lipid droplets from the endoplasmatic reticulum

Abstract: SummaryMost cells store neutral lipids in a dedicated compartment, the lipid droplet (LD). These LDs are structurally and functionally conserved across species. In higher eukaryotes, LDs are covered by abundant scaffolding proteins, such as the oleosins in plants and perilipins (PLINs) in animal cells. Saccharomyces cerevisiae, however, has no homologues of these scaffolding proteins. To analyze a possible function of these proteins in the biogenesis of LDs, oleosin and perilipin family members (PLIN1, ADRP/PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
102
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(125 citation statements)
references
References 54 publications
18
102
1
Order By: Relevance
“…3E). We have previously shown that the cytosolic PLINs are greatly enriched on isolated lipid droplets when expressed in yeast (Jacquier et al, 2013). A similar result was found for the signal-sequence-containing PLIN1-PLIN3 proteins (Fig.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…3E). We have previously shown that the cytosolic PLINs are greatly enriched on isolated lipid droplets when expressed in yeast (Jacquier et al, 2013). A similar result was found for the signal-sequence-containing PLIN1-PLIN3 proteins (Fig.…”
Section: Resultssupporting
confidence: 82%
“…Expression of PLINs in cells lacking neutral lipids, profoundly affected their subcellular localization. Instead of showing a punctate lipid droplet localization as observed in wild-type cells, the cytosolic PLINs showed a diffuse cytosolic distribution (Jacquier et al, 2013) (Fig. 2B).…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…There is even less known about how this signal (singular or plural) is/are specifically recognized at the droplet, and whether this recognition has its origin in a classical receptor/docking complex or is a product of the physicochemical nature of the droplet phospholipid monolayer and underlying neutral lipid core. Whatever the rules, this process is conserved: mammalian and plant droplet proteins can target efficiently in yeast and even induce droplet formation (Jacquier et al, 2013). There is evidence supporting the role of phospholipid density and surface tension on droplets controlling trafficking of proteins (Thiam et al, 2013b).…”
Section: Er To Droplet Traffickingmentioning
confidence: 99%